SIGNOS HISTOLOGICOS DE ELABORACION GLANDULAR EN LA PLACENTA I CELULAS GIGANTES - MANSILLA, MARGARITA (Instituto Nacional de Cardiología, CD MEXICO, DF, MEX, 1942)
White rats injected daily from 4 to 20 days of age with antuitrin-G showed a slightly greater increase in body wt and wt of the testicles than the controls Rats similarly injected with equine gonadotrophin showed no increase in body wt over the contro
BOL INST ESTUD MED BIOL
Keywords: SIGNOS, HISTOLOGICOS, ELABORACION, GLANDULAR, PLACENTA, CELULAS; CIENCIAS MEDICAS; BIOLOGIA HUMANA; HISTOLOGIA HUMANA